THE IMPACT OF GOLD PRICE FLUCTUATIONS ON INDONESIA’S ECONOMIC GROWTH: THE ROLE OF INFLATION, EXCHANGE RATE, AND INVESTMENT - Murti Widyaningsih; Adi Nugroho; Rika Kaniati; Ahmad Kurnia Ibrahim (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
This study examines the impact of gold prices on economic growth in Indonesia by incorporating inflation, exchange rate, and investment (Gross Fixed Capital Formation) as intervening variables. Using annual time series data from 2010 to 2025, the analysis applies the Autoregressive Distributed Lag (ARDL) approach to capture both short-run and long-run dynamics among the variables.The empirical results indicate the existence of a long-run equilibrium relationship among gold prices, inflation, exchange rate, investment, and economic growth. In both the short and long run, gold prices exhibit a statistically significant negative effect on economic growth. This suggests that rising gold prices tend to reduce economic performance throughthe reallocation of capital from productive sectors to safe-haven assets.Inflation and exchange rate depreciation are also found to negatively influence economic growth, while investment contributes positively and significantly to economic expansion. Furthermore, the results reveal that the effect of gold prices on economic growth operates not only directly but also indirectly through inflation, exchange rate, and investment channels, with investment identified as the strongest transmission mechanism.Overall, the findings highlight that the macroeconomic impact of gold prices is structurally mediated and highly dependent on investment behavior in emerging economies such as Indonesia.